Expanding Roles for CD4 T Cells and Their Subpopulations in Tumor Immunity and Therapy - Dobrzanski, Mark J. (Frontiers in Oncology, 2013)
The importance of CD4 T cells in orchestrating the immune system and their role in inducing effective T cell-mediated therapies for the treatment of patients with select established malignancies are undisputable. Through a complex and balanced array of direct and indirect mechanisms of cellular activation and regulation, this functionally diverse family of lymphocytes can potentially promote tumor eradication, long-term tumor immunity and aid in establishing and/or rebalancing immune cell homeostasis through interaction with other immune cell populations within the highly dynamic tumor environment. However, recent studies have uncovered additional functions and roles for CD4 T cells, some of which are independent of other lymphocytes, that can not only influence and contribute to tumor immunity but paradoxically promote tumor growth and progression. Here, we review the recent advances in our understanding of the various CD4 T cell lineages and their signature cytokines in disease progression and/or regression. We discuss their direct and indirect mechanistic interplay among themselves and with other responding cells of the antitumor response, their potential roles and abilities for "plasticity" and memory cell generation within the hostile tumor environment and their potentials in cancer treatment and adoptive immunotherapies.